Dinamika Self-Disclosure dalam Pengasuhan Digital: Analisis Peran Mediasi Teknologi pada Hubungan Parent Child Long Distance - Husna, Badiatul; Chusniyah, Tutut (Universitas Negeri Malang, 2025)
Long-distance parenting has become increasingly relevant in today's digital era, particularly with the rising mobility of parents due to work, education, or other personal circumstances. This phenomenon presents significant challenges in maintaining relationships between parents and children who are often separated by considerable physical distance. In this context, self-disclosure—the process by which individuals share personal information about themselves with others—emerges as an important aspect that needs to be analyzed. This study aims to understand the dynamics of self-disclosure in digital parenting within long-distance relationships between parents and children, highlighting the mediating role of digital technology. The method employed is a qualitative approach using snowball sampling. This technique begins with selecting a few initial respondents who meet the criteria, and then they recommend other relevant individuals to be included in the study. Data were collected through in-depth interviews with respondents, consisting of parents and children engaged in long-distance parenting. This study aims to explore how technology can facilitate or hinder the self-disclosure process between them. The findings are expected to provide new insights for researchers and practitioners in psychology and education regarding the importance of effective communication in digital parenting. Abstrak Pengasuhan jarak jauh (long distance parenting) menjadi semakin relevan di era digital saat ini, terutama dengan meningkatnya mobilitas orang tua akibat pekerjaan, pendidikan atau situasi pribadi lainnya. Fenomena ini memunculkan tantangan signifikan dalam menjaga hubungan antara orang tua dan anak yang sering kali terpisah oleh jarak fisik yang jauh. Dalam konteks ini, self-disclosure atau proses di mana individu berbagi informasi pribadi tentang diri mereka kepada orang lain menjadi aspek penting yang perlu dianalisis. Penelitian ini bertujuan untuk memahami dinamika self-disclosure dalam pengasuhan digital pada hubungan jarak jauh antara orang tua dan anak dengan menyoroti peran mediasi teknologi digital. Metode yang digunakan adalah pendekatan kualitatif dengan teknik snowball sampling. Teknik ini dimulai dengan memilih beberapa responden awal yang memenuhi kriteria, kemudian mereka merekomendasikan individu lain yang relevan untuk diikutsertakan dalam penelitian. Data dikumpulkan melalui wawancara mendalam terhadap responden yang terdiri dari orang tua dan anak yang menjalani pengasuhan jarak jauh. Penelitian ini jua bertujuan untuk mengeksplorasi bagaimana teknologi dapat memfasilitasi atau menghambat proses pengungkapan diri di antara mereka. Hasil dari penelitian ini diharapkan dapat memberikan wawasan baru bagi para peneliti dan praktisi di bidang psikologi serta pendidikan tentang pentingnya komunikasi yang efektif dalam pengasuhan digital.